Unveiling the role of surface, size, shape and defects of iron oxide nanoparticles for theranostic applications. Issue 34 (24th August 2021) - Cotin, Geoffrey; Blanco-Andujar, Cristina; Perton, Francis; Asín, Laura; de la Fuente, Jesus M.; Reichardt, Wilfried; Schaffner, Denise; Ngyen, Dinh-Vu; Mertz, Damien; Kiefer, Céline; Meyer, Florent; Spassov, Simo; et al.
Abstract : Theranosticity of nanoparticles provided by their shape, size, defects and dendron coating. Abstract : Iron oxide nanoparticles (IONPs) are well-known contrast agents for MRI for a wide range of sizes and shapes. Their use as theranostic agents requires a better understanding of their magnetic hyperthermia properties and also the design of a biocompatible coating ensuring their stealth and a good biodistribution to allow targeting of specific diseases. Here, biocompatible IONPs of two different shapes (spherical and octopod) were designed and tested in vitro and in vivo to evaluate their abilities as high-end theranostic agents. IONPs featured a dendron coating that was shown to provide anti-fouling properties and a small hydrodynamic size favoring an in vivo circulation of the dendronized IONPs. While dendronized nanospheres of about 22 nm size revealed good combined theranostic properties ( r 2 = 303 mM s −1, SAR = 395 W gFe −1 ), octopods with a mean size of 18 nm displayed unprecedented characteristics to simultaneously act as MRI contrast agents and magnetic hyperthermia agents ( r 2 = 405 mM s −1, SAR = 950 W gFe −1 ). The extensive structural and magnetic characterization of the two dendronized IONPs reveals clear shape, surface and defect effects explaining their high performance. The octopods seem to induce unusual surface effects evidenced by different characterization techniques while the nanospheres show high internal defects favoring Néel relaxation for magnetic hyperthermia. The study of octopods with different sizes showed that Néel relaxation dominates at sizes below 20 nm while the Brownian one occurs at higher sizes. In vitro experiments demonstrated that the magnetic heating capability of octopods occurs especially at low frequencies. The coupling of a small amount of glucose on dendronized octopods succeeded in internalizing them and showing an effect of MH on tumor growth. All measurements evidenced a particular signature of octopods, which is attributed to higher anisotropy, surface effects and/or magnetic field inhomogeneity induced by tips. This approach aiming at an analysis of the structure–property relationships is important to design efficient theranostic nanoparticles.